Penerapan Metode MABAC Pada Penerimaan Ahli Kesehatan dan Keselamatan Kerja (K3) - Angel P Simaremare (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
PT. Universal Gloves, a company engaged in the production of gloves, certainly requires occupational Health and Safety (K3) experts. Occupational health and safety (K3) experts must master their own field in the field of occupational health and safety (K3), therefore at PT. Universal Gloves requires an accurate selection process to accept occupational health and safety (K3) experts. Getting the results of the decision in the selection of occupational health and safety (K3) experts at PT. Universal Gloves is not easy because you have to choose occupational health and safety (K3) experts who really comply with PT. Universal Gloves, which have requirements based on predetermined criteria. Occupational Health and Safety (K3) is a field related to the health, safety and welfare of people who work in a company, among others, companies engaged in production. The purpose of occupational health and safety (K3) is to maintain the health and safety of the work environment. Occupational health and safety also protects co-workers, workers' families, consumers, and others who may also be affected by working conditions. To facilitate the leadership of PT. Universal Gloves make decisions in the selection process for the acceptance of occupational health and safety (K3) experts, a decision support system is needed for the admission of occupational health and safety (K3) experts at PT. Universal Gloves so as to provide accurate decision results in the acceptance of Occupational Health and Safety (K3) Experts at PT. Universal Gloves